Analisis Faktor Risiko Dominan terhadap Kejadian Demam Tifoid pada Kelompok Usia 5–19 Tahun di Wilayah Kerja Puskesmas Pulau Bunyu - Amatullah, Aisyah (LPPM Universitas Prima Nusantara Bukittinggi, 2025)
Typhoid fever remains a persistent public health concern in Indonesia, particularly in areas with limited access to clean water and sanitation. Bunyu Island in North Kalimantan is one of the endemic regions where typhoid fever consistently ranks among the top three reported infectious diseases. Children and adolescents aged 5–19 years are the most vulnerable group due to their higher level of outdoor activities, poor hygiene practices, and frequent exposure to unsafe food and beverages. This study aimed to analyze the dominant risk factors associated with typhoid fever incidence among individuals aged 5–19 years in the working area of Puskesmas Pulau Bunyu. This research employed a case control design with 120 respondents, consisting of 24 cases (diagnosed with typhoid fever within the last six months) and 96 controls (without typhoid fever during the same period). Data were collected through face-to-face interviews using validated structured questionnaires. The variables examined included demographic factors (age, gender, education, occupation, income), behavioral factors (handwashing with soap practices, snacking habits), environmental factors (availability of clean water facilities, provision of waste disposal facilities), and parental knowledge regarding typhoid fever. Data were analyzed using chi-square tests for bivariate analysis and multiple logistic regression for multivariate analysis. Bivariate analysis revealed significant associations with typhoid fever incidence for male gender (p=0.001; OR=6.059), poor handwashing with soap practices (p=0.002; OR=5.909), inadequate waste disposal facilities (p=0.025; OR=3.258), risky snacking habits (p=0.039; OR=3.128), and low parental knowledge (p=0.042; OR=2.931). Multivariate logistic regression identified four dominant risk factors: male gender (OR=5.863; 95% CI=1.828–18.801), poor handwashing with soap practices (OR=4.506; 95% CI=1.298–15.644), risky snacking habits (OR=4.181; 95% CI=1.305–13.395), and inadequate waste disposal facilities (OR=4.028; 95% CI=1.312–12.363). Together, these variables explained 38.3% of the variation in typhoid fever incidence. In conclusion, male gender, poor handwashing with soap practices, risky snacking habits, and inadequate waste disposal facilities are the primary determinants of typhoid fever incidence among children and adolescents aged 5–19 years in the Puskesmas Pulau Bunyu area. Strengthening health promotion, improving handwashing with soap practices, reducing unsafe snacking behaviors, and enhancing environmental sanitation particularly in waste management are essential strategies to reduce the burden of typhoid fever in high-risk populations.